EXPERIENCE IN DEVELOPING PROCEDURES FOR PROFESSIONAL AND PUBLIC ACCREDITATION FOR THE SOCIAL AND HUMANITARIAN SPHERE OF RUSSIAN EDUCATION - Alexander M. Dolgorukov; Vladimir V. Zyryanov; Philipp V. Malakhov; Larisa V. Temnova (Высшее образование в России)
The article presents the experience in development of the professional%public accreditation concept (PPA) of the higher education programs in the social and humanitarian sphere. The principles underlying the basis of this development are revealed.The paper dwells on the most important characteristics of process of education which have to be considered at an assessment of educational programs. Traditional and latest means of representation which are applied in modern educational process are considered.The concept and the main documents are developed taking into account the internationalexperience of accreditation. We discuss why the main qualities of the developed technology of accreditation will make it an important element of system of development of Russian education and increase its competitiveness in the international division of labor.